Keprihatinan masyarakat Melayu-Islam di Malaysia selepas pilihan raya umum ke-12 tahun 2008 - Nor, M.R.M.; Ngadiran, S.N.A.; Yusoff, B. (Fakultas Adab IAIN Ar-Raniry, Darussalam Banda Aceh, 2011)
Result of the 12th General Election in Malaysia held in March 2008 was shocking. For the first time, the ruling party since 1951, Barisan Nasional (BN), had lost a majority of two thirds of the parliament. Defeat of many BN candidates have opened the eyes of some people that anything can happen in the election voting process. The ruling party is aware that if the people who declined to support them is not handled properly, it will add badly in the next election. Conversely, some people see that the phenomenon of many victories for candidates who join the Pakatan Rakyat (PR) does not give a good impression, especially on the future of Malay-Muslim. However, the efforts made to convince people that the way of progress and development will continue to run. This article finds that there are those who are still doubtful about the ability of PR to fight for the nation, even though their leaders appeal to be given opportunity to rule the country and implement the manifesto by using different approach to the existing government.